Alterações da default mode network provocadas pela ingestão de Ayahuasca investigadas por Ressonância Magnética Funcional - Fontes, Fernanda Palhano Xavier de (2012)
Ayahuasca is psychotropic beverage that has been used for ages by indigenous populations in South America, notably in the Amazon region, for religious and medicinal purposes. The tea is obtained by the decoction of leaves from the Psychotria viridis with the bark and stalk of a shrub, the Banisteriopsis caapi. The first is rich in N-N-dimethyltryptamine (DMT), which has an important and well-known hallucinogenic effect due to its agonistic action in serotonin receptors, specifically 5-HT2A. On the other hand, β-carbolines present in B. caapi, particularly harmine and harmaline, are potent monoamine oxidase inhibitors (MAOi). In addition, the tetrahydroharmine (THH), also present in B. caapi, acts as mild selective serotonin reuptake inhibitor and a weak MAOi. This unique composition induces a number of affective, sensitive, perceptual and cognitive changes in individuals under the effect of Ayahuasca. On the other hand, there is growing interest in the Default Mode Network (DMN), which has been consistently observed in functional neuroimaging studies. The key components of this network include structures in the brain midline, as the anterior medial frontal cortex, ventral medial frontal cortex, posterior cingulate cortex, precuneus, and some regions within the inferior parietal lobe and middle temporal gyrus. It has been argued that DMN participate in tasks involving self-judgments, autobiographical memory retrieval, mental simulations, thinking in perspective, meditative states, and others. In general, these tasks require an internal focus of attention, hence the conclusion that the DMN is associated with introspective mental activity. Therefore, this study aimed to evaluate by functional magnetic resonance imaging (fMRI) changes in DMN caused via the ingestion of Ayahuasca by 10 healthy subjects while submitted to two fMRI protocols: a verbal fluency task and a resting state acquisition. In general, it was observed that Ayahuasca causes a reduction in the fMRI signal in central nodes of DMN, such as the anterior cingulate cortex, the medial prefrontal cortex, the posterior cingulate cortex, precuneus and inferior parietal lobe. Furthermore, changes in connectivity patterns of the DMN were observed, especially a decrease in the functional connectivity of the precuneus. Together, these findings indicate an association between the altered state of consciousness experienced by individuals under the effect of Ayahuasca, and changes in the stream of spontaneous thoughts leading to an increased introspective mental activity